2020
DOI: 10.1088/1755-1315/431/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Hour-ahead photovoltaic power forecast using a hybrid GRA-LSTM model based on multivariate meteorological factors and historical power datasets

Abstract: Owing to the clean, inexhaustible and pollution-free, solar energy has become a powerful means to solve energy and environmental problems. However, photovoltaic (PV) power generation varies randomly and intermittently with respect to the weather, which bring the challenge to the dispatching of PV electrical power. Thus, power forecasting for PV power generation has become one of the key basic technologies to overcome this challenge. The paper presents a grey relational analysis (GRA) and long short-term memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The data sets were created with identical time window sizes and proportions to ensure a uniform experimental environment. To benchmark the proposed model, we compared it with various statistical models such as ARIMAX, exponential smoothing (ES), and GPR [19], which are well-suited for large datasets, as well as machine learning-based models including XGBOOST [26], SVM[100], and deep learning-based models such as CNN [28], LSTM [29], GRU [30], LSTM-Attention(LSTM-A) [31], CNN-LSTM [32], and ConvLSTM [33]. The parameters of all algorithms in the comparison test are optimized for this situation, and the significant hyperparameter settings of all the models mentioned above are shown in TABLE IV.…”
Section: Comparative Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The data sets were created with identical time window sizes and proportions to ensure a uniform experimental environment. To benchmark the proposed model, we compared it with various statistical models such as ARIMAX, exponential smoothing (ES), and GPR [19], which are well-suited for large datasets, as well as machine learning-based models including XGBOOST [26], SVM[100], and deep learning-based models such as CNN [28], LSTM [29], GRU [30], LSTM-Attention(LSTM-A) [31], CNN-LSTM [32], and ConvLSTM [33]. The parameters of all algorithms in the comparison test are optimized for this situation, and the significant hyperparameter settings of all the models mentioned above are shown in TABLE IV.…”
Section: Comparative Experimentalmentioning
confidence: 99%
“…Further analysis of the basic weather types, such as sunny, cloudy, and rainy, is carried out using readily available meteorological data [14], [15], [16]. To find a method that can obtain appropriate training samples under various complicated weather conditions, indicators such as cosine similarity [17], Euclidean distance [18], and gray correlation [19] are often adopted to evaluate the similarity among samples. Furthermore, historical samples whose indicators are higher than the threshold value are selected as training sets and verification sets to analyze the similarity of PV power between the forecast day and the historical sample.…”
Section: Introductionmentioning
confidence: 99%
“…When predicting the fertilization of forests, Chen et al [32] discovered that the gray relation analysis-particle swarm optimization-back-propagation (GRA-PSO-BP) model was more reliable than the BP and BP-PSO models. Chen and Lin [33] found that the GRA-LSTM model was robust in the short-term forecasting of PV power plants. Chen et al [34] developed the GRA-NARX model to forecast changes of dissolved oxygen mass concentration in surface water; however, the model's accuracy tends to decline with time.…”
Section: Introductionmentioning
confidence: 99%